One-pot fluorescent labeling protocol for complex hydroxylated bioactive natural products - Haldar, Saikat; Kumar, Santosh; Kolet, Swati P.; Patil, Harshal S.; Kumar, Dhiraj; Kundu, Gopal C.; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2013)
Tagging of small bioactive molecules with a fluorophore is a highly sensitive method to trace their cellular activities through real-time visual information. Here we disclose a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based, high-yielding, one-pot labeling protocol for hydroxylated molecules using Yamaguchi coupling as the key reaction. This methodology was successfully applied on several sensitive and complex hydroxylated bioactive compounds including 7-deacetylazadiradione, simvastatin, camptothecin, andrographolide, cinchonine, beta-dihydroartemisinin, and azadirachtin A. Further, utility of this protocol was illustrated on the cytotoxic activity of azadiradione derivatives against several cancer cell lines through cell imaging of two qualified fluorescent probes.

Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.

Fungal mediated kinetic resolution of racemic acetates to (R)-alcohols using fusarium proliferatum - Jadhav, Dipesh D.; Patil, Harshal S.; Chaya, Patil S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Fungal mediated kinetic resolution of seven acyclic/aromatic acetates was achieved using Fusarium proliferatum to furnish (R)-alcohols in high enantiomeric excess (>95%). The kinetic resolution was established as one-pot two-step de-esterification/oxidation biocatalytic process. Further, the preparative scale synthesis of (R)-(+)-1-phenylethanol was accomplished through de-esterification/oxidation of (+/-)-1-phenylethyl acetate using the whole cell of F. proliferatum NCIM 1105. (C) 2016 Elsevier Ltd. All rights reserved.

Notch1-MAPK signaling axis regulates CD133+ cancer stem cell-mediated melanoma growth and angiogenesis - Kumar, Dhiraj; Kumar, Santosh; Gorain, Mahadeo; Tomar, Deepti; Patil, Harshal S.; Radharani, Nalukurthi N. V.; Kumar, Totakura V. S.; Patil, Tushar V.; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (Journal of Investigative Dermatology, 2016)
Functional characterization and understanding of the intricate signaling mechanisms in stem-like cells is crucial for the development of effective therapies in melanoma. We have studied whether melanoma cells are phenotypically distinct and hierarchically organized according to their tumorigenic nature. We report that melanoma-specific CD133(+) cancer stem cells exhibit increased tumor-initiating potential, tumor-endothelial cell interaction, and lung metastasis. These cells are able to transdifferentiate into an endothelial-like phenotype when cultured under endothelial differentiation-promoting conditions. Mechanistically, Notch1 upregulates mitogen-activated protein kinase activation through CD133, which ultimately controls vascular endothelial growth factor and matrix metalloproteinase expression in CD133(+) stem cells leading to melanoma growth, angiogenesis, and lung metastasis. Blockade or genetic ablation of Notch1 and mitogen-activated protein kinase pathways abolishes melanoma cell migration and angiogenesis. Chromatin immunoprecipitation and reporter assays revealed that Notch1 intracellular domain regulates CD133 expression at the transcriptional level. Andrographolide inhibits Notch1 intracellular domain expression, Notch1 intracellular domaindependent CD133-mediated mitogen-activated protein kinase and activator protein-1 activation, and epithelial to mesenchymal-specific gene expression, ultimately attenuating melanoma growth and lung metastasis. Human malignant melanoma specimen analyses revealed a strong correlation between Notch1 intracellular domain, CD133, and p-p38 mitogen-activated protein kinase expression and malignant melanoma progression. Thus, targeting Notch1 and its regulated signaling network may have potential therapeutic implications for the management of cancer stem cell-mediated melanoma progression.

Lipase catalyzed synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh; Paul, Ajay; Mulani, Fayaj Alam; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Data in Brief, 2018)
In this data article we describe screening of various lipases for the regioselective acylation of Andrographolide. Each lipase was screened with seven acyl donors. Amano lipase AK from Pseudomonas fluorescens was used for the synthesis of two new acylated andrographolide derivatives. Two new compounds, andrographolide-14-propionate and andrographolide-14-caproate were characterized by various spectral studies. These two derivatives showed more antimicrobial activity than andrographolide.

Regioselective and efficient enzymatic synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh D.; Paul, Ajay; Mulani, Fayaj A.; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Bioorganic & Medicinal Chemistry Letters, 2018)
Labdane diterpene andrographolide (1) is a major constituent of Andrographis paniculata and known to exhibit wide spectrum of biological activities. In this study, regioselective monoesters of (1) have been synthesized by using Amano lipase AK (Pseudomonas fluorescens) as a biocatalyst. Amano lipase AK was able to execute highly efficient esterification of hydroxyl group attached to C-14 carbon of (1) in presence of acyl donors. Among the various synthesized derivatives including two novel compounds such as andrographolide-14-propionate (3) and andrographolide-14-caproate (5) displayed antimicrobial activity against Staphylococcus aureus with low minimal inhibitory concentration (MIC) 4 mu g/mL and 16 mu g/mL respectively. Furthermore, they have shown low hemolysis activity at their respective MIC and increase in the permeability of the bacterial cell membrane as delineated by FITC uptake and SEM imaging studies. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Andrographolide; Antimicrobial activity; biocatalysis; Hemolysis; Lipase; Natural product

Design, synthesis of anticancer and anti-inflammatory 4-(1-methyl-1H-indol-3-yl)-6-(methylthio) pyrimidine-5-carbonitriles - Bhale, Pravin S.; Chavan, V. Hemant; Shringare, Sadanand N.; Khedkar, Vijay M.; Tigote, Radhakrishna M.; Mali, Nikita N.; Jadhav, Tukaram D.; Kamble, Nitin B.; Kolat, Swati P.; Bandgar, Babasaheb P.; Patil, Harshal S. (Synthetic Communications, 2022)
A novel series of 4-(1-methyl-1H-indol-3-yl)-6-(methylthio) pyrimidine-5-carbonitriles (4a-i) was synthesized and evaluated for anticancer potential against cell lines for breast cancer. Compounds 4b, 4e, and 4h exhibited prominent cytotoxicity against human breast carcinoma MCF-7 cell line with GI(50 )of 2.0, 0.5, and 0.5 mu M, respectively. Molecular docking study against EGFR tyrosine kinase could provide valuable insights into the plausible mechanism of action. The compounds could bind with significantly high binding affinity and their binding affinity scores could correlate well with the observed anticancer activity. Furthermore, compounds 4a, 4c, 4e, 4g, and 4i exhibited significant inflammatory activities as well which could expand the therapeutic domain of this novel series.
Keywords: Anti-inflammatory; Anticancer; Antioxidant; Indole; pyrimidine

Supramolecular self-assembly of glochidonol: a renewable triterpenoid from glochidion tomentosum - Patil, Harshal S.; Jagadeesh, K. S.; Dinore, Jaysingh; Sharanappa, P.; Baviskar, Ashwini S.; Thulasiram, Hirekodathakallu V. (Chemistryselect, 2025)
Glochidonol a lupane pentacyclic (6-6-6-6-5) triterpenoid isolated from Glochidion tomentosum, exhibited exceptional gelation ability compared to the screened lupane- and oleanane-type triterpenoids. This study represents the first report on the self-assembly behavior of glochidonol in various liquids. The molecule self-assembled to form gels in all tested aromatic solvents, whereas no gelation was observed in water or phosphate buffer. The structural and physical properties of the self-assembled glochidonol were characterized using optical microscopy, scanning electron microscopy, atomic force microscopy, and Fourier-transform infrared spectroscopy. Additionally, the glochidonol-based self-assembled fibrillar network was utilized for the encapsulation of fluorescein isothiocyanate as a model drug, highlighting its potential for biomedical applications. A glochidonol-based gel loaded with doxorubicin exhibited sustained, diffusion-mediated drug release into PBS, accompanied by partial gel degradation. Fluorescence analysis confirmed release suggesting drug-gel interactions and diffusion. The glochidonol-based gel demonstrated sustained, diffusion-controlled doxorubicin release with partial degradation under physiological conditions.
Keywords: Glochidion tomentosum; Glochidonol; Organo gelator; Self-assembly; Triterpenoids